The Need for a Senior Level Theory Seminar. - Smith, James E. (The Accounting Review, 1972)
The article discusses the need for a senior level theory seminar in accounting education. The author believes that a senior level theory seminar is a must for the accounting major. Discussion and correspondence with former students and with their employers in public accounting tend to support this opinion. The accounting practitioner is the one who decides upon implementation of change in accounting. Intense exposure to accounting theory increases the probability that the practitioner will initiate needed change. In establishing the classroom atmosphere, two approaches are available: provide direction for the class by having the professor serve as a discussion leader or leave the direction to the students by having the professor–serve as a moderator. Two requisites for the course are class size and room arrangement. A small class size is conducive to achievement of the course purposes. However, some minimum parameter probably is beneficial also. The room arrangement should be one in which the students face one another, enabling the class to quickly overcome the tendency for the student to address the professor rather than his peers.